2015
DOI: 10.1080/13608746.2015.1051758
|View full text |Cite
|
Sign up to set email alerts
|

Losers' Second Chances and Control of the Party Machine: Aspirant Premiers in Regional Spain

Abstract: In parliamentary democracies controlling party machines has traditionally been a key asset for nascent political leaders to continue in their position if they have suffered a bad electoral start. Recent proposals suggest, however, that this is no longer the case in 'old democracies', but the extent of its continuing importance in 'young' ones is still unclear. Based on a dataset built by the author of the candidates from the main national parties for the premiership of the Spanish Comunidades Autónomas, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Likewise, reselection is more likely when having lost the contest but still improved the party's electoral performance (Taylor & Boatright 2005). Loser candidates also tend to get another shot when being the party leader (Astudillo 2015). This notwithstanding, research on gender and political parties has shown that female party leaders have a greater likelihood of stepping down when their parties lose vote share (O'Brien 2015;O'Neill & Stewart 2009).…”
Section: Reselectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, reselection is more likely when having lost the contest but still improved the party's electoral performance (Taylor & Boatright 2005). Loser candidates also tend to get another shot when being the party leader (Astudillo 2015). This notwithstanding, research on gender and political parties has shown that female party leaders have a greater likelihood of stepping down when their parties lose vote share (O'Brien 2015;O'Neill & Stewart 2009).…”
Section: Reselectionmentioning
confidence: 99%
“…As a result, works on top executive leaders have tended to focus on women, but the reason why the ways in which political careers may be gendered cannot be fully grasped. For its part, mainstream research on executives has concentrated on elected presidents and prime ministers rather than on actual candidates (Botella et al 2010;Carreras 2017;Siavelis & Morgenstern 2008;Samuels & Shugart 2010; but see Astudillo 2015) or it has focused on party leaders under the assumption that the latter tend to be the executive candidates (Sandri et al 2015). For its part, mainstream research on executives has concentrated on elected presidents and prime ministers rather than on actual candidates (Botella et al 2010;Carreras 2017;Siavelis & Morgenstern 2008;Samuels & Shugart 2010; but see Astudillo 2015) or it has focused on party leaders under the assumption that the latter tend to be the executive candidates (Sandri et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations